Uterine parameters of clinical importance in North Indian females of reproductive age - An ultrasonographic evaluation - Aruna Arya; Sushma Tomar; Rakesh Kumar Diwan; Amita Pandey; Punita Manik (Wolters Kluwer Medknow Publications, 2021)
Introduction: The uterine size is important during planning of assisted reproductive techniques and hysterectomy and there is no established normative data from the women of northern India, this study was undertaken with the objective to report the normal length, width and anteroposterior lengths of non-gravid uterus. Methodology: In a prospective observational study, conducted in Department of Anatomy in collaboration with Departments of Radiology, Obstetrics and Gynecology of King George's Medical University, Lucknow, the ultrasonographic measurements of non-gravid uterus were noted. The ultrasonography was performed on females in dorsal decubitus position having full urinary bladder. Uterine position was identified by placing the probe on suprapubic area Length and anteroposterior diameter of uterus were measured by placing the probe in longitudinal direction (sagittal plane). Length was measured from fundus to external os. The anteroposterior diameter is maximum measurement in mid sagittal plane of body of uterus. The transducer was rotated up to 90 degree to measure the transverse diameter. Transverse diameter is the maximum measurement in transverse plane across the fundus. The volume of uterus was calculated. Results: The study included transabdominal ultrasonographic measurements of 100 females of age range 19-49 years (mean age 34.06 ± 0.35 years). Mean length, transverse diameter, anteroposterior diameters and volume noted were 7.71 (±0.47) cm, 4.63 (±0.33) cm, 3.75 (±0.31) cm and 70.54 (± 9.68) cm3. Conclusion: Normative values of uterine length, width and anteroposterior diameters of one-hundred non-pregnant women of northern India reported. Accurate measurement of uterine parameters is useful in timely management of various pathologies associated with abnormal size of uterus, infertility related procedures; such as in-vitro fertilization (IVF), embryo transfer (ET) and intrauterine device insertion.